PENERAPAN PENDEKATAN PEMBELAJARAN VISUALIZATION AUDITORY KINESTETHIC (VAK) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 181 PEKANBARU - Desra Wahyuni; Mahmud Alpusari; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was held because of the low of science achievement offifth grade students of SDN 181 Pekanbaru. KKM (success criteria) assigned is 78 inthe school. The class consist of 37 students, who reached the KKM was just 14 students(37,84%). Whereas students who have not yet reached the KKM was 23 students(62.16%). Class average value was 58.91. To solve these problems then researcherimplement the learning approach of VAK. The purpose of this research is to improve thescience (IPA) learning achievement of fifth grade students of SDN 181 Pekanbaru withthe implementation of the learning approaches of VAK. The research results obtainedbasic score of average value was 58.91. Its increased 24.78% become 73.51 in cycle I.The average value of the students increased become 41.13% (83.14) In cycle II. On abase score of classical success learn IPA students is 37.84% (not succes) on cycle I.After the implement of VAK learning approach success studied classical students rosebecome 59.46% (not success) and success of classical learning of students increasedbecome 89.19% (success) in cycle II. The activity of the teacher in the first meeting ofthe cycle I was 62.50% by enough category. The second meeting was increased become75.00% by enough category. And at the third meeting of the cycle I rose become81.25% with good categories. At the first meeting of the cycle II teacher activityincreased to 87.50% by category. At the second meeting increased become 93.75% bycategory. The activity of the students at the first meeting of the cycle I was 56.25% byless category. In The second meeting increased become 62.50% with enough categories,and at the third meeting of the cycle I increased become 81.25% with good categories.At the first meeting of the cycle II activity of students increased become 87.50% by verygood category. At the second meeting increased become 93.75% by very good category.From this research it can be concluded that by the implementation of visualizationauditory kinestethic (vak) learning approach can improve science achievement of fifthgrade students of SDN 181 Pekanbaru.Keywords: VAK Approach, learning achievement science